Problematika Pembelajaran Ilmu Balāghah di Kelas XI Madrasah Āliyah Pondok Pesantren Modern Al-Mu’minien Lohbener Indramayu - Sani, Ana Mutiara; Yusron Hidayat; Ahwil Lutan Hidayah (Mahira: Journal of Arabic Studies & Teaching, 2024)
This study aims to analyze and explain how the Balāghah Science learning system and process takes place, and what problems are faced by students in learning Balāghah Science, as well as what efforts are made to overcome the problems in learning Balāghah Science in Class XI of MA Al-Mu'minien. This study uses a qualitative approach with the type of research in the form of field research, or what is often known as "Field Research". The subjects in this study were students of class XI of MA Al-Mu'minien, Balāghah Science teachers, and the head of the Madrasah. Data collection in this study used observation, interview, and documentation methods. The results of this study are: 1)The Balāghah Science learning system in class XI MA Al-Mu'minien contains interrelated components. 2) The Balāghah Science learning process in class XI MA Al-Mu'minien uses lecture and question and answer methods. 3)The problems found in class XI MA Al-Mu'minien reviewed from the Balāghah Science learning process are linguistic problems and non-linguistic problems. 4)Efforts to overcome learning problems reviewed from the learning process are providing new vocabulary and synonyms, adding guidance, strengthening motivation, changing learning strategies, time discipline, adding special hours, reducing noise, adding facilities.